Reflection of Local Wisdom Values behind Accounting Practices in Tumbilotohe Culture - Thalib, Mohamad Anwar; Briando, Bobby (Institut Agama Islam Negeri Ponorogo, 2023)
This study explores the integration of local wisdom into accounting practices in the Tumbilotohe culture, framed within an Islamic paradigm and using an Islamic ethnomethodological approach. Data were collected through structured interviews, passive participant observation, and documentary analysis using a qualitative methodology. These were analyzed through the stages of charity, knowledge, faith, revelation information, and courtesy. The findings reveal that the Tumbilotohe Implementation Committee self-funded its activities through accounting practices that are deeply intertwined with values of sincerity, struggle, and sacrifice that are emblematic of the Gorontalo tribe's cultural and Islamic traditions. Central to these traditions is the vow